Activity and stability of enzyme immobilized with ionic liquid based polymer materials - Moniruzzaman, M. (Taylor's University, 2015)
Enzyme immobilization methods are continuously being developed for a wide range of applications including biocatalysis and biotransformation. Compared to other immobilization methods, physical entrapment into a matrix is relatively simple and inexpensive, and causes a relatively small perturbation to the native enzyme structure and function. However, significant enzyme leaching from such biocatalytic polymers is the main constraint in using them for industrial levels. This study reports an ionic liquid (IL) polymer materials incorporating enzymes that can be used as active, stable and reusable biocatalysts to overcome the limitations. Lipase was microencapsulated in surfactant aggregates formed in an IL monomer or the solution of an IL monomer/IL and then incorporated into polymer frameworks through the free radical polymerization of an IL (1-vinyl-3-ethylimidazolium bis(trifluoromethylsulfonyl) amide (veimTf2N). The activity, stability and reusability of IL polymer materials containing lipase were evaluated using lipase-catalyzed hydrolysis of p-nitrophenyl butyrate (p-PNB) as a model reaction. It was found that lipase IL polymer materials exhibited excellent stability in aqueous solutions. More importantly, these biopolymer materials retained most of their activity after six reaction cycles. We firmly believe that enzyme containing IL polymeric materials developed in this study will provide several advantages over conventional polymer based methods for diverse enzymatic reactions. Â© School of Engineering, Taylorâs University.